Theoretical and Computational Analysis of Confinement Regimes in Spherical ZnO, CdS, and CdSe Colloidal Quantum Dots - Harry, S. T. (Current Research Progress in Physical Science Vol. 7, 2025)
Quantum dots (QDs) exhibit unique optical and electronic properties due to quantum confinement effects, making them promising candidates for various applications. This study investigates the confinement regimes of colloidal spherical ZnO, CdS, and CdSe quantum dots through computational simulations and theoretical analysis. Confinement regimes were delimited for each of the quantum dots based on the exciton Bohr radius of carriers of the respective semiconductor. The results delineate size-dependent confinement effects, revealing critical size ranges for strong, intermediate, and weak confinement regimes and their associated energy levels. These findings provide valuable insights into optimising quantum dot performance for applications in optoelectronics, field-effect transistors, and photonic technologies, advancing the understanding of these semiconductor nanostructures.